Reconstruction of Islamic Brotherhood Values in Reducing Maladaptive Behavior in Islamic Boarding Schools - Totok Agus Suryanto; Madhar Amin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Maladaptive behavior is behavior that tends not to be accepted by the environment and society. Because this behavior is seen as detrimental to individual development. This maladaptive behavior is also found in the environment of IDIA Prenduan male ma'had students in the form of calling friends bad names. This reflects the fragility of the sense of ukhuwah Islamiyah within the mahasantri. The purpose of this research is to find out how the implementation of the reconstruction of ukhuwah Islamiyah values in reducing maladaptive behavior in the IDIA Prenduan men's ma'had. This research uses descriptive qualitative method. Research results: The form of implementation of the reconstruction of ukhuwah Islamiyah values is in the form of direct reprimand, advising, holding discussions and cultums.